2019
DOI: 10.3389/fpsyt.2019.00320
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for the Lateral Habenula in Depressive Illness: Physiologic and Molecular Mechanisms

Abstract: Emerging preclinical and clinical evidence indicate that the lateral habenula plays a major role in the pathophysiology of depressive illness. Aberrant increases in neuronal activity in the lateral habenula, an anti-reward center, signals down-regulation of brainstem dopaminergic and serotonergic firing, leading to anhedonia, helplessness, excessive focus on negative experiences, and, hence, depressive symptomatology. The lateral habenula has distinctive regulatory adaptive role to stress regulation in part du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 50 publications
3
55
0
Order By: Relevance
“…to arousal, implying that isoflurane-induced anesthesia may require excitation of the LHb. This finding is in agreement with a recent study in propofol which sedative doses of propofol -induced an increase of c-Fos expression in the LHb, although propofol had no impact on the resting membrane potential of LHb neurons in acute slices (Gelegen et al, 2018). Both in vivo and in vitro electrophysiological experiments demonstrated that the extracellular activity of LHb neurons had a higher firing rate during the day than at night (Zhao and Rusak, 2005;Sakhi et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…to arousal, implying that isoflurane-induced anesthesia may require excitation of the LHb. This finding is in agreement with a recent study in propofol which sedative doses of propofol -induced an increase of c-Fos expression in the LHb, although propofol had no impact on the resting membrane potential of LHb neurons in acute slices (Gelegen et al, 2018). Both in vivo and in vitro electrophysiological experiments demonstrated that the extracellular activity of LHb neurons had a higher firing rate during the day than at night (Zhao and Rusak, 2005;Sakhi et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Lesion of the LHb induces a reduction in sleep rebound time after sleep deprivation (Zhang et al, 2016) and shortens the duration of hippocampal theta oscillations (Aizawa et al, 2013b). Novel research shows that lesions of LHb glutamatergic neurons heighten resistance to propofol-induced anesthesia, while selective activation of the LHb accelerates propofol anesthesia (Gelegen et al, 2018). These studies indicated that the LHb participated in sleep regulation and propofol anesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exposure to stressors facilitates long‐term potentiation in the LHb (Park et al, 2017). Accordingly, ongoing activation of the LHb by chronic stress and/or successive disappointments should result in aberrant LHb activity, signaling to an individual that the situation is worse than expected (Gold & Kadriu, 2019). This implies that a hyperactive LHb may play a prominent role in the pathophysiology of stress‐related psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing lines of preclinical and clinical evidence highlight a major role for the lateral habenula, an anti-reward centre, in the pathophysiology of depression. It is suggested that abnormal increases in neuronal activity in this region signal downregulation of brainstem dopaminergic and serotonergic firing, resulting in depressive symptomatology including anhedonia, helplessness and excessive focus on negative experiences ( Gold and Kadriu, 2019 ).…”
Section: Mechanistic Considerationsmentioning
confidence: 99%